2005
DOI: 10.1002/ajh.20369
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of deletional α-thalassemia by an oligonucleotide microarray

Abstract: A simple, fast, and highly reproducible protocol for detection of the three most common deletional a-thalassemias (--SEA , -a 3.7 , -a 4.2 ) using an oligonucleotide microarray was developed. PCR products were directly hybridized to the microarrays with different deletion-specific probes. Genotypes were determined by quantitative analysis of the fluorescent signals detected by fluorescence scanning. Blind assays on 400 samples validated the efficiency and specificity of the protocol. This method may be suitabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In the southern China population, ‐ ‐ SEA , ‐α 3.7 , and ‐α 4.2 are the most common α‐thalassemia mutations . Other α‐thalassemia deletional mutations such as ‐ ‐ 11.1 and ‐α 27.6 and the α‐globin gene triplication (ααα anti3.7 and ααα anti4.2 ) have also been detected .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the southern China population, ‐ ‐ SEA , ‐α 3.7 , and ‐α 4.2 are the most common α‐thalassemia mutations . Other α‐thalassemia deletional mutations such as ‐ ‐ 11.1 and ‐α 27.6 and the α‐globin gene triplication (ααα anti3.7 and ααα anti4.2 ) have also been detected .…”
Section: Introductionmentioning
confidence: 99%
“…In the southern China population, --SEA , -α 3.7 , and -α 4.2 are the most common α-thalassemia mutations (2,3,6). Other α-thalassemia deletional mutations such as -- 11.1 (7) and -α 27.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of our CMA, which was a high resolution SNP array, and traditional single-tube multiplex PCR results indicated that CMA could accurately detect HBA gene deletion. In previous studies, oligonucleotide microarrays with custom design probes were successfully used to detect both α-thalassemia and β-thalassemia 70 – 72 . Thus, we suggest that a tentative diagnosis of α-thalassemia should be considered in patients who underwent CMA testing because this is important for genetic counseling and prevention of α-thalassemia, particularly in populations where the disease is endemic.…”
Section: Discussionmentioning
confidence: 99%
“…The unknown DNA's are cut into pieces by restriction endonucleases and these DNA pieces are label with fluorescent markers. These are then allowed to react with tests of the DNA chip [59][60][61].…”
Section: Gel Image Shows the Multiplex Arms Pcr For Five Common Mutations: [A] Ivs 1-5 Mutation/normal; [B] Ivs 1-5 Mutation/normal; [C] mentioning
confidence: 99%